Repayment performance of microfinance in Bank Simpanan Nasional (BSN) Melaka / Nurizzati Othman - Othman, Nurizzati (Faculty of Business and Management, 2011)
The aim of microfinance is to help the poor and lower income group to get funds for their business activities and to improve their lives. Usually, the loans given are very small, in short term period, no collateral needed and required weekly repayment. However, repayment problems become the main obstacle for the microfinance institutions to continue providing microcredit services. Therefore, this paper tries to review the repayment problem of microcredit services offer by Bank Simpanan Nasional (BSN) in Melaka and what factor contribute to this repayment problem. This is important to make sure that any problem regarding repayment problem can be settled at the early stage to reduce the number of non-performing loan in BSN Melaka. To get this information, I make an in-depth interview with manager and staff of BSN Melaka. Close monitoring of and a close relationship with borrowers appear to be important for early detection of any problem. Another aspect that may be important is building up loyalty and developing reliability among members. A close and informal relationship with borrowers may also help in monitoring and early detection of problems that may arise in non-repayment of loans.